2014
DOI: 10.7860/jcdr/2014/9230.4703
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Infection By Chromobacterium Violaceum

Abstract: A 19-year-male attended the outpatient department of IMS and SUM hospital, Bhubaneswar, India in Septmber, 2013 with chief complaints of burning micturation, fever with chills since seven days and pain in lower abdomen for three days. He had no past history of similar symptoms or any significant ailments. Abdominal examination revealed mild supra pubic tenderness. He was empirically treated with amoxicillin-clavulanic acid for urinary tract infection after advising necessary investigations. Laboratory findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 8 publications
4
29
1
Order By: Relevance
“…The most common presenting symptoms of human Chromobacterium violaceum infection are fever, sepsis, skin lesions, abdominal pain, and clinical syndrome of localized skin and soft tissue infection, lymphadenitis and gastroenteritis [8,10,16]. During the infection progression bacteremia and disseminated infection involving various organ systems can result in urinary tract infection, arthritis, osteomyelitis, abscesses in lung, brain and other viscera, meningitis, endocarditis, endophthalmitis, otitis media, vaginitis, haemophagocytic syndrome and multi-organ failure [8,10,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most common presenting symptoms of human Chromobacterium violaceum infection are fever, sepsis, skin lesions, abdominal pain, and clinical syndrome of localized skin and soft tissue infection, lymphadenitis and gastroenteritis [8,10,16]. During the infection progression bacteremia and disseminated infection involving various organ systems can result in urinary tract infection, arthritis, osteomyelitis, abscesses in lung, brain and other viscera, meningitis, endocarditis, endophthalmitis, otitis media, vaginitis, haemophagocytic syndrome and multi-organ failure [8,10,16].…”
Section: Discussionmentioning
confidence: 99%
“…During the infection progression bacteremia and disseminated infection involving various organ systems can result in urinary tract infection, arthritis, osteomyelitis, abscesses in lung, brain and other viscera, meningitis, endocarditis, endophthalmitis, otitis media, vaginitis, haemophagocytic syndrome and multi-organ failure [8,10,16].…”
Section: Discussionmentioning
confidence: 99%
“…2 A total of 154 cases of C. violaceum have been previously published. Location data available for 143 cases reveal a worldwide tropical distribution comprising western Pacific (Vietnam, Japan, Korea, Cambodia, Malaysia, China, Australia, Singapore, Laos, and Papua New Guinea) with 49 cases (34.3%), [3][4][5][6][7][8][9][10][11][12] the Americas with 46 cases (30.0%), 3,13,14 southeast Asia (Thailand, India, Sri Lanka, and Nepal) with 23 cases (16.0%), 3,[15][16][17][18][19][20][21][22] Africa with 22 cases (15.4%), 23,24 Persian Gulf with two cases (1.4%), 25 and Europe with one case (0.7%).…”
Section: Introductionmentioning
confidence: 99%
“…3 The review of the literature revealed only six cases of Chromobacterium infection in adults from India. [5][6][7][8][9][10] Among them only two case reports have documented C. violaceum septicemia. 5,9 The outcome was fatal in one case, 5 but unknown in the other case.…”
Section: Discussionmentioning
confidence: 99%